Design optimization of gas-to-liquid biosludge management systems - Mostafa, Rana (AUC Knowledge Fountain, 2015)
Biosludge is a solid waste byproduct of wastewater treatment. The biosludge treatment and management system represents an independent treatment stream in a wastewater treatment plant (WWTP). The system includes several treatment units that may occupy a large part of the wastewater treatment plant and significantly adds to its capital and running cost. The re-use of the processed biosludge or its disposal affects how it is treated and managed. The optimum management system of biosludge varies according to the type of wastewater generating the biosludge, applicable environmental legislations as well as site and climate conditions. Designing an optimum management system for biosludge generated from plants treating wastewater of Gas-To-Liquid (GTL) plants is important in many areas, such as the Gulf area. In cases where the GTL plant is located in an area that has high land cost, warm arid climate and a lack of sludge re-use markets, a biosludge management system that is optimized for such conditions is needed. Literature on the optimization of biosludge management systems is rather limited, although design codes exist that deal with conventional sludge management systems generated from municipal wastewater treatment plants. This research consists of two parts: (i) experimental investigation of the characteristics of GTL biosludge and its aerobic treatability, and (ii) developing a design model to obtain the optimum design of biosludge management systems in general, and the GTL biosludge in particular. Biosludge generated from an existing GTL WWTP was investigated. Sludge samples were collected and analyzed for solid content. Lab results characterized the biosludge to have an organic content of more than 80% of its dry solids content qualifying digestion as an adequate volume reduction and stabilization technique. Aerobic digestion achieved solid content reduction values of as high as 70% in 9 weeks. Results indicate that the decay constant specific to the investigated GTL biosludge is 0.0145day-1. The design model consists of three sub-models: a sizing and design sub-model, a simulation sub-model, and a cost and optimization sub-model. The recommended treatment units for the GTL biosludge are Aerobic Digestion (AD), Dewatering by Centrifuge, and Drying Beds (DB). The design sub-model is used to size the AD, centrifuge and DB for selected values of residence times in the AD and DB. The simulation sub-model is then used to track the daily changes of the water and solids content of the inflow biosludge through the AD, centrifuge and DB accounting for the ambient temperature that varies on a daily basis throughout the whole year. The simulation-sub-model predicts the daily final sludge amounts collected from the DB and transported to the landfill (LF) for disposal. The cost and optimization sub-model generates the alternative designs that are sized by the design sub-model and calculates the capital and operating costs based on the results of the simulation sub-model for each design alternative. Two main design variables are varied to identify the optimum design: residence time in the AD and time spent in the DB. The minimum cost alternative is chosen as the optimal treatment line-up recommendation. The minimum cost is a trade-off between the cost of biosludge being aerated for a longer time and the drying and disposal cost savings achieved by smaller volumes of produced biosludge. The model was applied to obtain the optimum management system for a daily feed of 360 tons of GTL biosludge under five cases: (i) minimum cost, (ii) with constraint on the daily disposal amount of 20 tons, (iii) potential re-use of processed sludge, (iv) domestic biosludge, and (v) refinery biosludge applications. The optimum design for case (i) did not include the AD as its cost was higher than the reduction in cost of the subsequent treatment units. The design comprised of the centrifuge, drying beds (for 8 days), transportation and disposal to LF. This alternative results in 20.3 tons/day at a unit cost of $7.26/ton. The design for case (ii) ensured a rate of disposed sludge of less than 20 tons to meet the EPA requirement hence required an AD with a residence time of 21 days plus 8 days in the DB with a unit cost of $9.97/ton. Case (iii) suggested a solution for GTL biosludge to qualify for the land application requirement based on 28 days of residence time in the aerobic digester and one day in the drying beds. This would result in 16.9 tons/day at unit cost of $10.69/ton. Cases (iv) and (v) deal with domestic and refinery biosludges that have higher decay constants resulting in a drop in amounts and costs of biosludge produced to 16.8 tons/d of sewage sludge costing $6.01/ton and 10.21 tons/d of refinery sludge costing $4.55/ton. The model gives results on an average of one year but allows the versatility of monitoring seasonal performances and varying the design accordingly.